Cyanamide (NH2CN) in interstellar medium: Potential spectral lines - Sharma, M. K. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Cyanamide (NH2CN) has pyramidal equilibrium structure with two substates, denoted by 0+ and 0-. For each state of NH2CN, knowing rotational and centrifugal distortion constants in conjunction with electric dipole moment, energies for rotational levels and the probabilities for radiative transitions between the levels are calculated. Цианамид (NH2CN) имеет пирамидальную структуру равновесия с двумя подсостояниями, обозначенными 0+ и 0-. Для каждого состояния NH2CN, зная константы вращательного и центробежного дисторсий в сочетании с электрическим дипольным моментом, вычислены энергии вращательных уровней и вероятности радиационных переходов между уровнями.
Keywords: Stars